2017
DOI: 10.1002/2017gl076244
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel‐3A Views Ocean Variability More Accurately at Finer Resolution

Abstract: This is the first multiplatform evaluation involving data from the new Sentinel-3A altimeter. An experiment was undertaken in the Algerian Basin, employing an ocean glider and a ship mission, along the same track and synchronous with an overpass of the Sentinel-3A mission. This provided three independent views of the ocean velocity field, along a section that encompassed three different oceanographic regimes. The results demonstrate the capacity of Sentinel-3A to retrieve fine-scale oceanographic features (~20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The Sentinel‐3 altimeter (red lines in Figure ) uses delayed Doppler (or synthetic aperture radar) processing (European Organisation for the Exploitation of Meteorological Satellites, ; Raney, ), which is designed to achieve significantly higher signal‐to‐noise ratios (Heslop et al, ). However, Sentinel‐3's Sun‐synchronous orbit, with a 27‐day repeat, is distinct from that of previous altimeters (cf.…”
Section: Methodsmentioning
confidence: 99%
“…The Sentinel‐3 altimeter (red lines in Figure ) uses delayed Doppler (or synthetic aperture radar) processing (European Organisation for the Exploitation of Meteorological Satellites, ; Raney, ), which is designed to achieve significantly higher signal‐to‐noise ratios (Heslop et al, ). However, Sentinel‐3's Sun‐synchronous orbit, with a 27‐day repeat, is distinct from that of previous altimeters (cf.…”
Section: Methodsmentioning
confidence: 99%
“…The main sources of noise come from the altimeter waveform retracking algorithms, instrumental noise, and geophysical variability within the altimeter footprint (Dibarboure et al, 2014;Sandwell & Smith, 2005;Thibaut et al, 2010). Analysis of fine-scale ocean dynamics then requires preliminary noise filtering (e.g., Heslop et al, 2017;Morrow et al, 2017). To analyze and filter the altimeter data, we use an approach described in Kopsinis and McLaughlin (2009), the key part of which is the nonparametric EMD (Huang et al, 1998;Wu & Huang, 2004).…”
Section: Methods: Emd Of Along-track Altimeter Datamentioning
confidence: 99%
“…New generations of SAR altimeter missions have demonstrated that compared to conventional altimetry (or low-resolution mode), this technique significantly reduces the measurements level of noise and improves the along-track spatial resolution (Boy et al, 2017). The comparison between altimetry, ocean gliders and ADCP showed a significant improvement, order 30% in resolution and 42% in velocity accuracy using a synthetic aperture radar mode with respect to lower-resolution mode of conventional altimetry (Heslop et al, 2017). Integrating the three datasets provided valuable insight into the variability of oceanographic features, in an area of the Mediterranean that remains chronically under sampled and has demonstrated benefits to improve knowledge on coastal and fine-scale dynamics.…”
Section: Opportunities For Integrationmentioning
confidence: 98%